Association Between Red and Processed Meat Consumption and Risk of Prostate Cancer: A Systematic Review and Meta-Analysis - Nouri-Majd, Saeedeh; Salari-Moghaddam, Asma; Aminianfar, Azadeh; Larijani, Bagher; Esmaillzadeh, Ahmad (Frontiers in Nutrition, 2022)
Background: Debate on the potential carcinogenic effects of meat intake is open and the relationship between meat consumption and risk of prostate cancer remains uncertain. This meta‐analysis was conducted to summarize earlier prospective studies on the association of meat consumption with risk of prostate cancer. Methods: Relevant studies were identified by exploring PubMed/Medline, Scopus, Web of Science, EMBASE, and Google Scholar databases up to December 2020. Fixed-effects and random-effects meta-analyses were used for pooling the relative risks (RRs). Heterogeneity across studies was evaluated using the Q-statistic and I-square (I2). A funnel plot and Egger's test was used to detect publication bias. Linear and non-linear dose-response analyses were performed to estimate the dose-response relations between meat intake and risk of prostate cancer. Results: Twenty-five prospective studies were included in this meta-analysis. Totally, 1,900,910 participants with 35,326 incident cases of prostate cancer were investigated. Pooling the eligible effect sizes, we observed that high consumption of processed meat might be associated with an increased risk of “total prostate cancer” (RR: 1.06; 95% CI: 1.01, 1.10; I2=1.5%, P=0.43) and “advanced prostate cancer” (1.17; 1.09, 1.26; I2=58.8%, P=0.01). However, the association between processed meat and “advanced prostate cancer” was not significant in the random-effects model: 1.12 (95% CI: 0.98, 1.29). A linear dose-response analysis indicated that an increment of 50 grams per day of processed meat intake might be related to a 4% greater risk of “total prostate cancer” (1.04; 1.00, 1.08; I2=0.0%, P=0.51). “Total meat intake” was marginally associated with all outcomes of prostate cancer risk (1.04; 1.01, 1.07; I2=58.4%, P<0.001). Conclusions: This systematic review and meta‐analysis of prospective studies indicated that increased consumption of “total meat” and “processed meat” might be associated with a higher risk of prostate cancer.